2018
DOI: 10.1097/nmd.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Conducting Long Term Follow Ups in Psychotherapy Research—Issues in the Literature and Data From a Randomized Therapy Comparison Study for Posttraumatic Stress Disorder

Abstract: Studies of psychotherapy for posttraumatic stress disorder (PTSD) typically encompass short follow-up periods, leading to a dearth of information on the long-term course of symptoms after treatment. We summarize existing long-term follow-up studies and highlight the issues making such research difficult. In this context, we report on a 2-year follow-up on a randomized treatment study comparing dialogical exposure therapy and cognitive processing therapy for adults with PTSD after type I trauma. Many of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…As early as 2006, Uwe Strumpfel published the first extensive review of Gestalt therapy studies and Willi Butollo' s classic trauma treatment research comparing dialogic exposure therapy (DET; a form of Gestalt therapy) with cognitive processing therapy with similar effect sizes. Interestingly, effect sizes and average scores tend to increase both in 6-month and 2-year follow-up for both treatments, and for all measures, but with slightly bigger changes in favor of DET, especially in measures for interpersonal stress and 2 years end of therapy (König et al, 2018).…”
Section: Future Directions For Gestalt Therapymentioning
confidence: 93%
“…As early as 2006, Uwe Strumpfel published the first extensive review of Gestalt therapy studies and Willi Butollo' s classic trauma treatment research comparing dialogic exposure therapy (DET; a form of Gestalt therapy) with cognitive processing therapy with similar effect sizes. Interestingly, effect sizes and average scores tend to increase both in 6-month and 2-year follow-up for both treatments, and for all measures, but with slightly bigger changes in favor of DET, especially in measures for interpersonal stress and 2 years end of therapy (König et al, 2018).…”
Section: Future Directions For Gestalt Therapymentioning
confidence: 93%
“…One study also reported significant long-term improvements in depression, PTSD and anxiety symptoms 2.5 years after a mindfulness-based stress reduction (MBSR) program for adult survivors of childhood sexual abuse (17), a therapy component that was also included in our multimodal treatment program (see Section "Treatment description"). But, some studies had important limitations concerning the sample [e.g., exclusion of patients after childhood sexual abuse in König et al (13)], which were overcome by the present examination.…”
Section: Introductionmentioning
confidence: 89%
“…There was no link to trauma type, population type (i.e., military vs. civilian) or intended duration of treatment, suggesting efficacy for a wide variety of patients. Other studies showed encouraging results for long-term efficacy for various groups of patients, outpatient treatment types and different follow-up intervals (e.g., EMDR, cognitive processing therapy, cognitive-behavioral therapy, written exposure therapy) (9)(10)(11)(12)(13)(14)(15)(16). One study also reported significant long-term improvements in depression, PTSD and anxiety symptoms 2.5 years after a mindfulness-based stress reduction (MBSR) program for adult survivors of childhood sexual abuse (17), a therapy component that was also included in our multimodal treatment program (see Section "Treatment description").…”
Section: Introductionmentioning
confidence: 99%